Матеріали до генеалогії Лазаревських, Герасимовських, Семенових та Колчевських з фондів Державного архіву Cумської області - Дегтярьов, С.І. (Сумський історико-архівний журнал, 2008)
For the first time there are published materials on genealogy of several known nobiliary kins of Leftbank Ukraine. The presented documents are stored in funds of konotop povit and povit zemstvo courts of State archive of Sumy region.